Nilai-Nilai Pendidikan yang Terkandung dalam Tradisi Malamang pada Masyarakat Kabupaten Padang Pariaman - Helmaiza Helmaiza; Ahmad Rivauzi (FONDATIA, 2022)
The purpose of this study is to determine the educational values contained in the Malamang tradition which includes the values of religious, social, moral and cultural education. As well as the implementation of the Malamang tradition. This research is a qualitative research with phenomenology research method. Data were obtained using interview, observation and documentation techniques. Data analysis includes data reduction, data presentation and drawing conclusions. The results of the study show that the educational values contained in the Malamang tradition in the people of Padang Pariaman Regency already exist, but some people still believe in this Malamang tradition as a ritual to mediate the safety of people who have meningeal. The Malamang tradition basically contains the cultural values of its bearer (Minangkabau) which should be inherited by today's society, such as the values of spiritual education (remembering to die and patience), social (cooperation, mutual cooperation), moral (unity and unity) and culture, because making lamang is done jointly by the community